Aspects of Tracking in the Schools as a Factor of Risk and Exclusion of Students - Israel, Lili (Wydawnictwo Naukowe UAM, 2017)
The tracking of students in the schools is a topic that obligates social and educational reference. This is a fieldthat exposes gaps and contradictions regarding the possibilities and intentions of parts of Israeli society. It is difficultto definewho is being talked about. In addition, it is difficultto separate between or limit the reference to the single student as a real and feeling subject and the desire of the system for a child as a product of education. It is difficultto describe a general picture without forgetting the individuals in it, the students, when the relationship between the tracking, the dropping out, and the exclusion is unavoidable.This article is an attempt to examine the argument presented in research studies that the gaps between different groups in the population derive from the policy of tracking in education from the establishment of the State of Israel until today and that this policy is intentional. The way that the school as an organization acts and the topics with which it copes can be explained in social policy and in the sociological rationale that characterizes society in Israel.Which social and educational policy serves the tracking of students and why, despite the data and the numbers that indicate a large gap, is the topic of tracking not present in the educational discussion? I seek to assert that research in the field is insufficient and thait is necessary to place the topic on the agenda and conduct an educational discussion.
Dzielenie dzieci w szkole na grupy pod względem możliwości intelektualnych jako czynnik ryzyka i wykluczenia
Keywords: youths at-risk; tracking; exclusion; inequality in education; social structures; separation; differentiation; transcription; segregation